Phosphoglucomutase A-mediated metabolic adaptation is essential for antibiotic and disease persistence in Mycobacterium tuberculosis - Taruna Sharma; Shaifali Tyagi; Rahul Pal; Jayendrajyoti Kundu; Sonu Kumar Gupta; Vishawjeet Barik; Vaibhav Kumar Nain; Manitosh Pandey; Prabhanjan Dwivedi; Bhishma Narayan Panda; Yashwant Kumar; Ranjan Kumar Nanda; et al. (mSystems)
ABSTRACT The long-term survival of Mycobacterium tuberculosis (Mtb) requires efficient use of host resources and uninterrupted access to host-derived nutrients. This is done by utilization of a highly flexible and integrated network of metabolic pathways. Phosphoglucomutase A (pgmA) is essential for glycogen biosynthesis, which acts as a nutrient reservoir and is known to modulate carbon flux in various pathogens. We, for the first time, investigated the role of pgmA in Mtb by creating a strain lacking this gene. The absence of pgmA hinders the survival of pathogens under nutrient-limiting and reactivation conditions. Our study shows that the lack of cell membrane-associated glycolipids in ΔpgmA compromises cell wall integrity and increases susceptibility to stress. Interestingly, ΔpgmA exhibits an enhanced growth phenotype on cholesterol compared to the wild type due to low cyclic adenosine monophosphate (cAMP) levels. Differential gene expression and 13C3 carbon dilution analyses indicate that stored carbon as glycogen is crucial for Mtb survival under nutrient-limiting conditions. We demonstrate that pgmA is vital for Mtb growth within the host. This study highlights the critical role of pgmA in metabolic adaptation during nutrient starvation and reactivation and its implication on antibiotic and disease persistence. These insights are crucial for developing novel, shorter, and more effective anti-tuberculosis strategies.IMPORTANCEThis study for the first time investigated the role of metabolic enzyme phosphoglucomutase A (pgmA) in Mycobacterium tuberculosis (Mtb), revealing its crucial functions as a toggle switch between biosynthesis and growth. This work highlights the importance of pgmA in maintaining the metabolic flexibility of Mtb during the nutritional switch. The presence of pgmA is critical for the production of membrane-associated glycolipid, which helps maintain the cell wall integrity under various growth and stress conditions. This adaptability is pivotal for generating starvation-induced antibiotic tolerance in Mtb. In addition to the clinical context, these findings provide a mechanistic foundation for understanding adaptive strategies by Mtb to harsh environments and the development of drug-tolerant bacilli.